2001
DOI: 10.1037/0022-006x.69.3.552
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a prevention program for teenagers on sexual coercion: A differential effectiveness approach.

Abstract: The authors evaluated a coeducational program for teenagers on preventing sexual coercion in dating situations. Students examined individual and social attitudes underlying coercive sexual behavior and learned communication skills aimed at preventing or dealing with unwanted sexual advances. Instruction was enhanced by video and an interactive video "virtual date." Outcomes were assessed using sexual attitude scales with a sample of 458 high school students. Student health education classes were randomly assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
1
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 40 publications
(81 reference statements)
1
82
1
5
Order By: Relevance
“…43,44,[57][58][59] Eight papers include multiple testing of data for analyses that were apparently determined post hoc, making at least some of the analyses exploratory rather than confirmatory. Some of these do not report correction for multiple testing or the processes used for this are unclear, [45][46][47][48]60 while others report at least some correction for this. 49,60,61 Technically, the findings arising from the pilot studies and from the exploratory findings should only be used for generating hypotheses for future studies, as they are not designed to provide definite answers to the questions they pose.…”
Section: Quantitative Studies: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…43,44,[57][58][59] Eight papers include multiple testing of data for analyses that were apparently determined post hoc, making at least some of the analyses exploratory rather than confirmatory. Some of these do not report correction for multiple testing or the processes used for this are unclear, [45][46][47][48]60 while others report at least some correction for this. 49,60,61 Technically, the findings arising from the pilot studies and from the exploratory findings should only be used for generating hypotheses for future studies, as they are not designed to provide definite answers to the questions they pose.…”
Section: Quantitative Studies: Resultsmentioning
confidence: 99%
“…Nine distinct trials were reported among the 13 papers; eight of these used some kind of clustering design. Eight were based in the USA (reported in nine papers) [43][44][45][46][47][48][49]53,54 and one in Canada (reported in two papers). 50,56 The date range was 1997-2013.…”
Section: Quantitative Studies: Resultsmentioning
confidence: 99%
See 3 more Smart Citations